Within- and Between-Subject Variation in Dietary Intake of Fermentable Oligo-, Di-, Monosaccharides, and Polyols Among Patients with Irritable Bowel Syndrome - Nybacka, Sanna; Storsrud, Stine; Liljebo, Therese; Neve, Boris Le; Tornblom, Hans; Simren, Magnus; Winkvist, Anna (Current developments in nutrition, 2019)
Background: A diet low in fermentable carbohydrates, fermentable oligo-, di-, monosaccharides, and polyols (FODMAPs) is a promising treatment option for patients with irritable bowel syndrome (IBS). In order to correctly estimate and study the intake of FODMAPs, information about within- and between-subject variations in intakes is needed, but is currently lacking. Objectives: The aim was to characterize the variation in FODMAP intake among patients with IBS and to calculate how many days of observations are required to capture absolute intakes as well as to rank individuals. Methods: Food intake was recorded during 4 consecutive days, and intakes of energy and FODMAPs were calculated. The coefficient of variation within subjects (C[V.sub.w]), coefficient of variation between subjects (C[V.sub.b]), number of days required to estimate an individual's intake, and number of observations required to correctly rank individuals into quartiles of consumption were calculated. Results: Diet records were provided from 151 women and 46 men with IBS. The reported mean energy intake was 2039 [+ or -] 502 kcal among women and 2385 [+ or -] 573 kcal among men, and the median FODMAP intakes were 18.7 g (range 3.7-73.4) and 22.8 g (range 3.6-165.7), respectively. The ratio of C[V.sub.w]/C[V.sub.b] for total FODMAP intake was 0.83 for women and 0.67 for men, and below 1 for all FODMAPs. To capture intake of FODMAPs at the individual level, 19 d of observations are required. Ranking individuals within a group would require 2-6 d of observations. Conclusion: There is more variation between subjects than within subjects regarding FODMAP intake. To correctly estimate an individual's absolute intake of FODMAPs, the number of days of diet records required exceeds what is reasonable for a participant to accomplish. However, ranking individuals into quartiles of FODMAP consumption can be achieved using a 4-d food record. This trial was registered at www.clinicaltrials.gov as NCT02107625 and NCT01252550. Curr Dev Nutr 2018;3:nzy101.